PENGEMBANGAN RPP MATEMATIKA DENGAN PROBLEM BASED LEARNINGBERBASIS PENDIDIKAN KARAKTERPADA MATERI DIMENSI TIGA - Volisa, Metra; Kurnia, Lely; Zulmardi, Zulmardi (Jurnal Pembelajaran MIPA, 2014)
This development research aimed to result mathematics lesson plan with PBL base educatinal character valid and practice. This lesson plan develop used 4-D modelÂ which modified beccome 3-D. In thisÂ research data colleting by using validation sheet, observation sheet, interview guidance, practicality questionnaire, and student evaluation sheet. Technic of analysis data of validation result, questionnaire observer of criticÂ and creative character is statistic descriptive. Mean while result of observation to logic thinking charackter, interview, and self evaluation analized with descriptive. Result of research show that lesson plan are fulfill valid and practice criterion also can develop student logic thinking, critic, and creative character.Key words: lesson plan development, Problem Based Learning (PBL),Character education